Asian Journal of Gerontology and Geriatrics 2020
DOI: 10.12809/ajgg-2018-326-oa
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to advance care planning programmes targeting older care home residents: a qualitative study

Abstract: Background. Advance care planning (ACP) is considered to be an integral part of end-of-life care. This study explored the facilitators and barriers of ACP by consolidating the practice experiences of a group of healthcare professionals involved in an outreach end-of-life programme for older people living residential care homes for the elderly (RCHEs). Methods: Fourteen healthcare professionals participated in this qualitative study. They first completed a questionnaire to capture their views on ACP by describi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…With an ageing population in Hong Kong, it is desirable to promote advance care planning and advance directives in older people so that their healthcare wishes are better understood. 20 CHF was safe in suitable patients with dysphagia; only 6% had pneumonia after CHF. This is comparable to a study in Singapore that reported a rate of aspiration pneumonia of 7.7% in patients with dysphagia who refused nasogastric tube feeding and had oral feeding.…”
Section: Discussionmentioning
confidence: 84%
“…With an ageing population in Hong Kong, it is desirable to promote advance care planning and advance directives in older people so that their healthcare wishes are better understood. 20 CHF was safe in suitable patients with dysphagia; only 6% had pneumonia after CHF. This is comparable to a study in Singapore that reported a rate of aspiration pneumonia of 7.7% in patients with dysphagia who refused nasogastric tube feeding and had oral feeding.…”
Section: Discussionmentioning
confidence: 84%
“…There is growing evidence of the potential effectiveness of advance care planning in nursing homes (42)(43)(44)(45). Relatives have been identi ed as one of ve key facilitators of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional support, reassurance, and space for sharing personal feelings provided within terminal care interventions are valued by patients at EoL and their families. [31][32][33] It could also imply that as patients became more at peace with impending death, their mood improved, and their physical distress decreased.…”
Section: Reported Outcomes Of Changes In Symptomsmentioning
confidence: 99%